2014
DOI: 10.1007/s40685-014-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

HR development in local government: how and why does HR strategy matter in organizational change and development?

Abstract: Human resource (HR) management has been proposed as being one of the core drivers of the modernization of the public sector, in particular with reference to the changing nature of people management and ‘HR-public service partnerships’ as an antecedent capacity of modernizing public service organizations. Notwithstanding the ongoing interest in the transformation of HR systems, this study explores how and why such relationships between HR management (HRM) and organizational change emerge. Considering a resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
(176 reference statements)
0
6
0
Order By: Relevance
“…The Municipal Systems Act (Act 32 of 2000) defines a municipality as an organ of state within the local sphere of government, exercising legislative and executive authority within the area determined in terms of the local government: Municipal Demarcation Act, 1998. Bruns (2014) argued that local government can potentially derive valuable organisational outcomes in terms of efficiency gains or public service improvements when their human resource policies and practices strengthen a sustainable human resource development. Shreeve et al (2012) opined that Workforce Planning is done to maximise the returns from the large investment in skills and tertiary qualifications, stressing that it is not enough to concentrate only on the supply of skills and competencies.…”
Section: Human Capital Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Municipal Systems Act (Act 32 of 2000) defines a municipality as an organ of state within the local sphere of government, exercising legislative and executive authority within the area determined in terms of the local government: Municipal Demarcation Act, 1998. Bruns (2014) argued that local government can potentially derive valuable organisational outcomes in terms of efficiency gains or public service improvements when their human resource policies and practices strengthen a sustainable human resource development. Shreeve et al (2012) opined that Workforce Planning is done to maximise the returns from the large investment in skills and tertiary qualifications, stressing that it is not enough to concentrate only on the supply of skills and competencies.…”
Section: Human Capital Developmentmentioning
confidence: 99%
“…In Nigeria, effective manpower planning is important because it assists the local government to acquire enough quantity and quality of manpower needed for effective use; to plan training and career development; and provide for the future manpower needs of the organisation in terms of skills needed. Bruns (2014) added that learning and development are required for temporary workers, after training, they become as skilful and competent as regular workers and that their performance is comparable to those of the regular workers when considering important industrial variables such as quality. Without sufficient budget, some critical skills might not be obtained by employees and that will affect their performance and service delivery.…”
Section: Innovation and Organisational Performancementioning
confidence: 99%
“…HR actors in public sector organisations have considerable autonomy and are the guardians of professional HR practice (Bruns, 2014). They place value on standardised guidelines when making HR decisions and may perceive TM as something that falls outside their remit (Jacobson and Sowa, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Budhwar, Al-Yahmadi, Debrah (2002) highlighted the growing emphasis on human resource development (HRD) and the strategic approach to such HRD initiatives at a national level in Omani firms. Bruns (2014) evidenced that the forces of either strategic or administrative patterns refer to different layers and the sequencing of HRM activities within a process of HR system change.Uyar&Deniz (2012) investigated the -Entrepreneur Support Programme‖ in Turkey and confirmed that the human resource management practices and procedures could help the entrepreneurs to navigate their companies elevating the economy to a higher level. The above literature review guidelines the perspectives of the study towards human resource, capital investment through local procurement and local community development.…”
Section: Icv Backs Small and Medium Enterprises (Smes)mentioning
confidence: 99%